PENGARUH KEPUASAN KERJA TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA KARYAWAN PT TELKOM TEGAL - Panggalih, Bening; Zulaicha, Ratni (Performance, 2012)
The aims of research are first to analyze the effect of job satisfaction on organizational citizenship behavior, to analyze the effect of motivation on organizational citizenship behavior, to analyze the effect of job satisfaction on organizational citizenship behavior and to analyze the effect of motivation on relationship between job satisfaction and organizational citizenship behavior at PT. Telkom Tegal. The research was conducted at the office of PT. Telkom Tegal. Number of respondents in the research is 48 employees. Which is the sampling technique used in this research is probability sampling (selected sample), whereas determination of sample size using Slovin formula. To test hypotheses in this research, it has used simple and multivariate regression analysis. Based on the result of simple regression analysis, it has got the value of computed-t is greater than value of ttable, therefore the first, second and third hypothesis is accepted. The results of multivariate regression analysis showed that direct effect coefficient of job satisfaction on organizational citizenship behavior is 73.54 percent, while the coefficient of the indirect effect of job satisfaction on organizational citizenship behavior through motivation decreased to 48.14 percent, therefore the fourth hypothesis is accepted. Based on the result of data analysis, it can be concluded that job satisfaction has significant effect on organizational citizenship behavior, motivation has significant effect on organizational citizenship behavior, job satisfaction has significant effect on organizational citizenship behavior and motivation mediated on relationship between job satisfaction and organizational citizenship behavior at PT. Telkom Tegal.